2011
DOI: 10.2134/jeq2010.0458
|View full text |Cite
|
Sign up to set email alerts
|

Losses of Surface Runoff, Total Solids, and Nitrogen during Bermudagrass Establishment on Levee Embankments

Abstract: Nutrient and sediment runoff from newly constructed levee embankments pose a threat to water quality during soft armor vegetation establishment. Research was initiated in 2008 and 2009 to evaluate the effect of bermudagrass ( L.) coverage and N source on nutrient and sediment runoff from levee embankments during establishment. Bermudagrass plots were seeded at 195.3 kg pure live seed ha and fertilized at 50 kg N ha using a water-soluble N source, urea or NH-NO, or slow-release N source, S-coated urea (SCU) or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Sediment losses from buff er strips receiving runoff from concrete pavement declined from 1.7 × 10⁻ 2 Mg ha⁻ 1 yr⁻ 1 as Kentucky bluegrass was establishing to 3.5 × 10⁻ 3 Mg ha⁻ 1 yr⁻ 1 in the second year after seeding (Steinke et al, 2008). Burwell et al (2011) showed that sediment losses from embankments declined from approximately 2 Mg ha⁻ 1 to less than 0.2 Mg ha⁻ 1 during the fi rst 70 d of bermudagrass establishment. The establishment rate was unaff ected by nitrogen fertilizer, although soluble nitrogen sources contributed to nitrogen loading in the runoff .…”
Section: Sediment and Nutrientsmentioning
confidence: 98%
“…Sediment losses from buff er strips receiving runoff from concrete pavement declined from 1.7 × 10⁻ 2 Mg ha⁻ 1 yr⁻ 1 as Kentucky bluegrass was establishing to 3.5 × 10⁻ 3 Mg ha⁻ 1 yr⁻ 1 in the second year after seeding (Steinke et al, 2008). Burwell et al (2011) showed that sediment losses from embankments declined from approximately 2 Mg ha⁻ 1 to less than 0.2 Mg ha⁻ 1 during the fi rst 70 d of bermudagrass establishment. The establishment rate was unaff ected by nitrogen fertilizer, although soluble nitrogen sources contributed to nitrogen loading in the runoff .…”
Section: Sediment and Nutrientsmentioning
confidence: 98%
“…In this study, runoff initiation occurred within 3.3 to 5.5 min, with runoff volumes ranging from 40.9 to 50.3 L (depth, 2.9-3.6 cm) across all rainfall simulations with no effect resulting from fertilizer treatment. Other studies that have examined nutrient losses from turfgrasses via surface runoff correlated factors such as sward density (Easton and Petrovic, 2004;Gross et al, 1990) and groundcover (Burwell et al, 2011) to variation in runoff initiation, volumes, and sediment loading. Prostrate-growing turfgrass species, such as hybrid bermudagrass, form dense canopies that obstruct water flow for greater infiltration, delay the onset of runoff, decrease runoff volume, and trap sediment (Burwell et al, 2011;Easton and Petrovic, 2004;Linde and Watschke, 1997).…”
Section: Resultsmentioning
confidence: 99%
“…If the practice of increasing N fertility did not accelerate bermudagrass sprig growth for faster canopy closure, then it is important to understand other potential benefits or drawbacks associated with higher N application. Areas in the mid‐South, such as Louisiana, where annual precipitation can exceed 150 cm yr −1 (US Climate Data, 2019), sediment and nutrient losses will occur during establishment on fine‐textured soils due to low plant density (Burwell et al, 2011) and high soil moisture, a result of routine irrigation applied to prevent sprig desiccation. A dense turfgrass can delay the onset of surface runoff to reduce runoff volume and pollutant transport (Cole et al, 1997; Gross et al, 1990; Morvan et al, 2014) due to greater water infiltration, tortuous flow path, and entrapment of suspended sediments (Burwell et al, 2011; Linde and Watschke, 1997), as has been illustrated by the collective data in this study (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Offsite movement of nutrients from various horticultural and agronomic crops has been extensively reported (Baker and Laflen, 1982;Bilderback, 2002;Easton and Petrovic, 2004;Nicholaichuk and Read, 1978;Shuman, 2002;Zhu et al, 1989). However, for turfgrass, dense coverage reduces surface runoff and traps suspended sediments to minimize pollutant transport (Burwell et al, 2011;Gross et al, 1991;Krenitsky et al, 1998;Morvan et al, 2014). Sward density greatly affects the occurrence and severity of runoff and thus nutrient movement (Easton and Petrovic, 2004).…”
mentioning
confidence: 99%